Selecting a data element in a network - Hassan Awadalla, Hany; Madkour, Amgad M. (2010)
One embodiment of the disclosure can represent within a K-partite graph, weighting factors between a set of identifier elements and a set of data elements. The K-partite graph can also represent weighting factors between the set of identifier elements and a set of metadata elements. In the K-partite graph, the set of identifier elements, the set of data elements, and the set of metadata elements are independent and disjoint sets such that no two vertices within a same set are adjacent. A score vector can be calculated that ranks each data element in a set of data elements. The score vector can be calculated from the weighting factors. At least one data element from the set of data elements can be selected using the score vector and a predetermined selection criterion.
US Patent US8589412B2